2022
DOI: 10.3390/genes13111967
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the Fecal Metagenome and Metabolome in Bladder Cancer in a Chinese Population

Abstract: Bladder cancer (BLCA) is a common malignancy of the urinary system. The gut microbiome produces various metabolites that play functional roles in tumorigenesis and tumor progression. However, the integrative analysis of the gut microbiome and metabolome in BLCA has still been lacking. Thus, the aim of this study was to identify microbial and functional characteristics and metabolites in BLCA in a Chinese population. Metagenomics, targeted metabolomics, bioinformatics, and integrative analysis were used in feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…In addition, they found a reduction in probiotics in bladder cancer patients, such as Lactobacillus , Bifidobacterium , and Butyrate-producing bacterium , which are believed to be crucial in protecting the body and inhibiting tumor growth. 37 In our study, we found no differences in the gut microbiome between bladder cancer patients and healthy controls, but the ANCOM analysis showed a difference between bladder cancer patients by sex and tumor grade. However, due to the small number of groups, further research is needed.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, they found a reduction in probiotics in bladder cancer patients, such as Lactobacillus , Bifidobacterium , and Butyrate-producing bacterium , which are believed to be crucial in protecting the body and inhibiting tumor growth. 37 In our study, we found no differences in the gut microbiome between bladder cancer patients and healthy controls, but the ANCOM analysis showed a difference between bladder cancer patients by sex and tumor grade. However, due to the small number of groups, further research is needed.…”
Section: Discussioncontrasting
confidence: 64%
“…While 3-methoxytyrosine might regulate immune cell responses by modulating enzyme activities, the latter's role remains elusive but could be tied to neurotransmitter pathways and their influence on allergic reactions. 32 , 33 In the realm of cofactors and vitamins, threonate emerged with its association, potentially reflecting its antioxidant capabilities or its integral role in collagen synthesis in ocular tissues, 34 both of which can be pivotal in maintaining ocular health during allergenic assaults. Interestingly, the xenobiotic, metoprolol acid metabolite, underscores the possible interactions between medication metabolites and AC, suggesting that certain drug breakdown products could modulate the allergic response, 35 either by influencing immune responses or by altering ocular tissue's receptivity to allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports previous observational evidence. A metagenomic analysis from China found dysregulated Eubacterium abundance in the gut of bladder cancer patients [ 39 ]. In another cohort study, upregulation of Eubacterium abundance in urine was associated with non-muscle invasive bladder cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%